1998
DOI: 10.1093/ajcn/67.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of lactulose-induced diarrhea by psyllium: effects on motility and fermentation

Abstract: Psyllium has been reported to inhibit lactulose-induced colonic mass movements and to benefit patients with irritable bowel syndrome, improving both constipation and diarrhea. Our aim was to define how psyllium modified the whole-gut transit of a radiolabeled lactulose-containing test meal by using gamma scintigraphy. Eight subjects participated in a randomized crossover study comparing gastric emptying and small bowel and colonic transit after consumption of 20 mL lactulose three times daily with or without 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 30 publications
2
39
0
1
Order By: Relevance
“…decreasing the viscosity of hard stool in constipation (softer stool, increased transit rate, improved bowel movement frequency), and increasing the viscosity of loose/liquid stool in diarrhea (firmer stool, slower transit rate, less frequent bowel movements) [3,[66][67][68] . The gel-forming, water-holding capacity of psyllium has been shown to soften hard stool better than docusate, a marketed stool softener [59] , and to firm loose/liquid stool in diarrhea, normalizing stool form [66][67][68] .…”
Section: Ge Intesmentioning
confidence: 99%
See 1 more Smart Citation
“…decreasing the viscosity of hard stool in constipation (softer stool, increased transit rate, improved bowel movement frequency), and increasing the viscosity of loose/liquid stool in diarrhea (firmer stool, slower transit rate, less frequent bowel movements) [3,[66][67][68] . The gel-forming, water-holding capacity of psyllium has been shown to soften hard stool better than docusate, a marketed stool softener [59] , and to firm loose/liquid stool in diarrhea, normalizing stool form [66][67][68] .…”
Section: Ge Intesmentioning
confidence: 99%
“…The gel-forming, water-holding capacity of psyllium has been shown to soften hard stool better than docusate, a marketed stool softener [59] , and to firm loose/liquid stool in diarrhea, normalizing stool form [66][67][68] . The stool normalizing benefit (e.g.…”
Section: Ge Intesmentioning
confidence: 99%
“…The husk obtained after milling is white hydrophilic material forming clear and colorless mucilaginous gel after water absorption. Psyllium seed husk is composed of mucilaginous polysaccharides, with a highly branched acidic arabinoxylan containing a xylan backbone (Washington et al, 1998 andBlumenthal et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, psyllium was used for the controlled delivery of peptides such as insulin [22] . It has been shown that psyllium could reduce the concentration of low-density lipoprotein (LDL) and cholesterol in the plasma, [23] and can be used in the treatment of irritable bowel syndrome (IBS), [24][25][26][27] maintaining remission in ulcerative colitis, [28,29] and inhibiting carcinogenic processes. [30,31] Psyllium not only has pharmacological importance but it also can be used to develop drug delivery devices such as sustained release matrix tablets and hydrogels.…”
Section: Introductionmentioning
confidence: 99%